1993
DOI: 10.1111/j.1748-1716.1993.tb09538.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic influence on the excitability of antidromically activated Renshaw cells in the lumbar spinal cord of the rat

Abstract: The interaction between dopaminergic and cholinergic systems in the mammalian central nervous system, which is thought to have important implications in the pathophysiology of major extrapyramidal disorders, has never been adequately demonstrated in vivo. Renshaw cell burst responses to single electrical shocks to lumbar ventral roots in spinalized and decerebrated rats were studied. In this monosynaptic cholinergic pathway, apomorphine, a dopaminergic receptor agonist, inhibited whereas the D2-antagonist sulp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…An important caveat is that DA may not have similar actions in different cells in the ventral horn. Heterogeneity of actions is a hallmark of monoaminergic modulatory actions in the spinal cord (Kemnitz, 1997;Beato and Nistri, 1998;Rekling et al, 2000;Schmidt and Jordan, 2000;Gordon and Whelan, 2006), and there is reason to suspect that DA may also have different effects on different classes of ventral horn neurons depending on DA receptor distribution (Dubois et al, 1986;Maitra et al, 1993;Seth et al, 1993;Levant and McCarson, 2001). In other regions of the brain, DA increases EPSCs in layer II-III pyramidal neurons (GonzalezIslas and Hablitz, 2003) in rat prefrontal cortex but decreases EPSCs in the nucleus of the solitary tract (Kline et al, 2002).…”
Section: Synaptic Transmissionmentioning
confidence: 99%
“…An important caveat is that DA may not have similar actions in different cells in the ventral horn. Heterogeneity of actions is a hallmark of monoaminergic modulatory actions in the spinal cord (Kemnitz, 1997;Beato and Nistri, 1998;Rekling et al, 2000;Schmidt and Jordan, 2000;Gordon and Whelan, 2006), and there is reason to suspect that DA may also have different effects on different classes of ventral horn neurons depending on DA receptor distribution (Dubois et al, 1986;Maitra et al, 1993;Seth et al, 1993;Levant and McCarson, 2001). In other regions of the brain, DA increases EPSCs in layer II-III pyramidal neurons (GonzalezIslas and Hablitz, 2003) in rat prefrontal cortex but decreases EPSCs in the nucleus of the solitary tract (Kline et al, 2002).…”
Section: Synaptic Transmissionmentioning
confidence: 99%
“…Dopamine enhances ventral horn field potentials during antidromic activation of motoneurons in rat lumbar spinal cord (53) but decreases the synaptic response to dorsal root stimulation in rat and cat motoneurons (189,777). In addition, dopamine modulates Renshaw cell-mediated feedback inhibition of rat motoneurons via effects of both D 1 -and D 2 -type dopamine receptors (778,1129). Intracellular studies on mammalian motoneurons are required to determine if mechanisms identified in lower vertebrates and invertebrates are retained in mammals.…”
Section: G Dopaminementioning
confidence: 99%
“…Even more surprising are the volunteers' responses to the treatment L-dopa+benzerazide. One hypothesis to account for this imbalance may involve the maintenance of a monosynaptic pathway, 17 capable of regulating the transmission of dopaminergic stimuli. Dopamine, by stimulating dopaminergic D 2 receptors, might inhibit central cholinergic transmission yielding a neurochemical balance (excitatory/inhibitory) which would prevent the occurrence of such abnormal movements.…”
Section: Discussionmentioning
confidence: 99%
“…Dopaminergic agonists have since been used in the treatment of movement disorders. Maitra 17 observed the involvement of the spinal cord in the pathophysiology of extrapyramidal motor disorders. There are motor nerve terminals containing muscarinic as well as inhibitory dopaminergic receptors that in¯uence acetylcholine release at the spinal cord level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation